Analysis of animation videos in online learning in class IV students of MI Imam Syafi'i - Prameswari, Noviardani Kartika; Ummah, Nasyrotul (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
This research aims to find out how to use video in online learning and find out obstacles in using animated videos in class IV MI Imam Syafi'I. Researchers used a qualitative approach with the teachers' assistance and fourth-grade students as subjects in the study. In collecting data using techniques, including observation techniques, interviews, questionnaires, and also documentation. For data analysis techniques used in researchers such as data reduction, data display, conclusion/drawing. Animated videos used by teachers when online learning are animated GIF types. The benefits of animated videos are to improve student understanding and increase student attractiveness during learning. Based on the research results, the use of media can help teachers to increase creative activities when carrying out learning activities so that students are not easily bored, lazy and students become excited and active when learning takes place online. Educators can see the understanding and enthusiasm of students through a questionnaire distributed by the homeroom teacher in the form of a link. Meanwhile, the delivery of material in online learning using animated videos has several obstacles during learning, such as inadequate signals and sometimes the student quota is also limited, so that making animated videos does not work well and the delivery of material in learning activities is also less than optimal